Assessment of transitory crops in cocoa (Theobroma cacao L) agroforestry in Páez, Boyacá - Alfonso-Alfonso, Lindays; Escobar-Pachajoa, Laura Dayana; Montealegre-Bustos, Felipe; Carvalho, Fabricio Eulalio; Carvajal-Rivera, Albert Sneyder; Rojas-Molina, Jairo (Revista de Ciencias Agrícolas, 2024)
Agroforestry systems incorporate several productive components per unit area to yield efficiency. However, considering the high degree of complexity inherent to interspecific plant-plant interactions, little is known about most of these systems' real productive potential and efficiency. In this context, it is important to analyze the interactions between the components to identify potential favorable associations. The objective of this research was to evaluate the performance of the transitory crops maize (Zea mays L) and cowpea (Vigna unguiculata L) in a family farming system under three agroforestry arrangements with cocoa in the municipality of Páez, Boyacá, Colombia. A split plot design was used, where the main plots corresponded to three shade forest species, which were associated with cocoa and the transient crops. The subplots corresponded to three planting systems: CS1cocoa+maize, CS2 coca+beans and CS3 cocoa+maize+beans. The effect on agronomic and productive traits of transitory crops (maize and beans) was evaluated, and an economic analysis was carried out. For beans, the effect of the cropping system on yield (t. ha-1) stood out, while for maize, the statistical effect was given by the forest x cropping system interaction in most of the variables evaluated. Considering the interspecific interactions found under the influence of different forests, the use of Colombian mahogany as a companion species in these intercropping systems is suggested. The cost analysis revealed that the maize-bean association is more efficient in the equivalent use of land. Therefore, the data obtained reveal more efficient strategies for sustainable cocoa productivity in Colombia.